NEUROPSYCHOMOTOR DEVELOPMENT IN FIRST INFANCY: ANALYSIS OF THE DAY CARE MUNICIPAL CENTERS OF FLORIANÓPOLIS (Fiep Bulletin - online, 2014)
Increase in woman insertion at the work market, as well as the voluntary search of socialization spaces for the children, has improving the importance of childhood education's institutions. Regarding the intense neuropsychomotors modifications that characterize childhood, its emergent to look at on the education professionals who work with this people. This work aimed to characterize the perception of educators that work in municipal day-care centers from Florianopolis on Neuropsychomotor Development and chances of its stimulation in babies of 0 to 24 months old. The sample group was composed by 55 educators of municipal day-care centers of Florianopolis. The choice of educators was by a random drawing regarding the roll of the institutions available in the Education Secretary's Office from Florianopolis (Childhood Education Department) Home Page. A questionnaire composed by 28 open and closed questions was used as research instrument. The data collection became fulfilled in the period of 2006 March to April. Statistical treatment data was made with software SPSS® version 13.0, and qualitative approach by content analysis. The data had been analyzed by descriptive statistics (average standard deviation, minimum and maximum value for quantitative variable; frequency and ratio for qualitative variable). The results had shown that the chances of neuropsychomotor stimulation at municipal day-care centers from Florianopolis are insufficient. Multiple factors had been observed that intervene in stimulation activities for children up to 2 years as the deficiency in educators professional formation, the lack of their specific knowledge, the lack of appropriate materials for the activities, among others. Continuation of this study is suggested, with bigger sample size, and comments about the environment of the day-care center and the practical ones of stimulation by educators.
Keywords: Neuropsychomotor Development (DNPM); Childhood; Day-care centers; Childhood Education